Preoperative endoscopy and pathology report of the specimen to be recommended in sleeve gastrectomy? - Alessandris, Remo; Moroso, Federico; Michelotto, Mauro; Fassan, Matteo; Angerilli, Valentina; Callegari, Linda; Foletto, Mirto (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Objective. Preoperative upper gastrointestinal endoscopy (UGIE) and postoperative histopathological examination (HPE) of resected specimens are still controversial issues in bariatric surgery. Methods. A retrospective review of prospectively collected laparoscopic sleeve gastrectomies (SG) performed at our institution for morbid obesity was carried out. All patients underwent pre-operative UGIE with biopsy, post-operative HPE and conventional postoperative follow-up. Results. From January 2019 through January 2021 we performed a total of 501 laparoscopic SG. A total of 12 (2.4%) neoplasms were found, 2 evident at preoperative UGIE, 4 detected during operation, and 6 at HPE. Eight of these 12 cases had some malignant potential and 5 would not have been detected without HPE of the specimen. The most significant unexpected case was a fundic gland type adenocarcinoma in a 64-year-old female with severe obesity. Conclusion. On the basis of our clinical experience, we recommend both preoperative endoscopic assessment and postoperative HPE of the specimen to provide the best available treatment to these patients.